Subdivisions of the sediment column, carbon and calcium carbonate at DSDP Hole 64-480 - LeClaire, Joseph P; Kelts, Kerry (Supplement to: LeClaire, JP; Kelts, K (1982): Calcium carbonate and organic carbon stratigraphy of late Quaternary laminated and homogeneous diatom oozes from the Guaymas Slope, HPC Site 480, Gulf of California. In: Curray, JR; Moore, DG; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 64, 1263-1275, https://doi.org/10.2973/dsdp.proc.64.168.1982, 1982)
We analyzed 580 integrated scrape-samples from HPC Site 480 for organic and carbonate carbon. Once precise dating is available, these will provide a high-resolution framework for understanding late Quaternary Oceanographic and climatic fluctuations in this region. Organic carbon ranges mostly within a narrow band of 1.8 to 3.5% C. Calcium carbonate varies from undetectable to over 20%, with an average of only about 5%. Source of carbonate are mostly benthic and planktonic foraminifers, although some sections are dominated by diagenetic carbonate, shelly hash, or nannofossils. Detrital sources are low in carbonate. We divided the sequence into 17 calcium carbonate (CC) zones to separate pulses, low and median values. The CC-Zones show various second-order patterns of cyclicity, asymmetry, and events. Laminated zones have lowest uniform values, but a perfect correlation between carbonate content and homogeneous or laminated facies was not found. Maximum values tend to be located near the transition of these two sediment types, showing that accumulation of carbonate is favored during times of breakdown of stable Oceanographic conditions.